High Performance Long Wavelength Superlattice Photodetectors Based on Be Doped Absorber Region - 周易 陈建新 徐志成 王芳芳 徐庆庆 许佳佳 白治中 靳川 何力 (Chinese physics letters, 2014)
The effect of Be doping on the quantum efficiency and the dark current of InAs/GaSb long-wavelength infrared superlattice photodetectors grown by molecular-beam epitaxy on GaSb substrates are reported. A significant improvement of quantum efficiency （QE） with p-type doping is demonstrated. Our results show that Be doping level at 2.5 × 10^15 cm^3 gives the highest quantum efficiency of product 28%. We also demonstrate that the increased QE is not only resulted from the longer minority carrier diffusion length, but also the p-n junction location change. Finally, the result also shows that the sample with a doping density of 2,5 × 10^15 cm^3 has the largest D＊ as 8.68 × 10^10 cm.Hz^l/2.W^-1, which is almost five times D＊ of the non-intentionally doped one.